Impedance pneumograph studies in left ventricular failure. Issue 6 (November 1967) - Tanser, A. R.
Abstract : Tidal volume can be measured by recording the change in impedance of the thorax caused by breathing. Thus breathing can be recorded quantitatively from two electrodes placed on each side of the chest. The method is especially useful in breathless patients and studies of breathing patterns during sleep. A patient with a long circulation time due to left ventricular failure had periodic breathing both awake and asleep. When asleep the respiratory minute volume was considerably reduced, and there were long apnoeic periods. This was associated with a rise in mean right atrial pressure until the patient woke with an attack of paroxysmal dyspnoea. The right atrial pressure dropped to normal when the patient breathed more regularly. Anoxia probably caused the rise in right atrial pressure. Periodic breathing disappeared when the circulation time shortened after treatment of the heart failure. The possible mechanism of these changes is discussed.